CONTRIBUTIONS FROM OTHER ORGANIZATIONS FOR THE PERIOD ENDED OCTOBER 31, 1993 (Tufts Archival Research Center, 2007)
List of financial contributions from organizations other than the Tobacco Institute to the Tobacco Industry Labor Management Committee (TILMC) until October of 1993.